Pemikiran Pendidikan At-Tahthawi - Rusadi, Bobi Erno; Yusri, Dairina (STAI Serdang Lubuk Pakam, 2019)
Al-Thahthawi's educational thought was motivated by his existence as a reformer in Egypt at that time. Al-Thahthawi made updates on all fields in Egypt, and one of them was in the field of education. Education is carried out not only for men, but also for women. And this education is done not only to broaden knowledge, but also to instill personality and instill a spirit of patriotism. As for some of his thoughts. The purpose of education according to al-Thahthawi is for the formation of personality, not only, not only for intelligence. Thinking about the curriculum that in addition to religious studies should also include modern sciences so that they can adapt the Shari'a to the needs of their time.